2006
DOI: 10.1007/s10329-006-0011-4
|View full text |Cite
|
Sign up to set email alerts
|

Visual search for orientation of faces by a chimpanzee (Pan troglodytes): face-specific upright superiority and the role of facial configural properties

Abstract: A previous experiment showed that a chimpanzee performed better in searching for a target human face that differed in orientation from distractors when the target had an upright orientation than when targets had inverted or horizontal orientation [Tomonaga (1999a) Primate Res 15:215-229]. This upright superiority effect was also seen when using chimpanzee faces as targets but not when using photographs of a house. The present study sought to extend these results and explore factors affecting the face-specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
63
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 73 publications
(114 reference statements)
11
63
0
1
Order By: Relevance
“…Tomonaga [24] found the inversion effect in one chimpanzee for unfamiliar human faces compared with houses (this was a different subject than in Tomonaga et al [15]) using a MTS task. Similar results were found using a visual search task where the same chimpanzee was significantly faster to identify an upright human face and a human caricature face among four or 10 differently oriented distracters [37]. No differences were found in the time required to find the target when the stimuli were upright chairs or hands presented against inverted distracters from the same stimulus categories.…”
Section: Part 1 (A) Configural Information In Facessupporting
confidence: 77%
See 1 more Smart Citation
“…Tomonaga [24] found the inversion effect in one chimpanzee for unfamiliar human faces compared with houses (this was a different subject than in Tomonaga et al [15]) using a MTS task. Similar results were found using a visual search task where the same chimpanzee was significantly faster to identify an upright human face and a human caricature face among four or 10 differently oriented distracters [37]. No differences were found in the time required to find the target when the stimuli were upright chairs or hands presented against inverted distracters from the same stimulus categories.…”
Section: Part 1 (A) Configural Information In Facessupporting
confidence: 77%
“…A follow-up study presented different facial features and combinations of features and showed an upright superiority effect for the eyes and eyebrows, the eyes and nose, and the eyes and mouth, but not the nose and mouth, or nose or mouth alone. A final study presented the inner features of the face, and the external contour, where faster identification times were found only for upright inner features when presented against inverted distracters [37].…”
Section: Part 1 (A) Configural Information In Facesmentioning
confidence: 99%
“…Some studies have reported evidence of the face inversion effect in monkeys and apes (Neiworth et al 2007, cotton-top tamarins;Overman and Doty 1982, pigtail macaques;Parr et al 1998;Parr and Heintz 2006;Tomonaga 1999Tomonaga , 2007Tomonaga 1994, Japanese macaques; Vermeire and Hamilton 1998, rhesus monkeys), while others have failed to find evidence of orientation-specific processing exclusive for faces (Bruce 1982;Dittrich 1990, longtail macaques; Gothard et al 2004;Parr et al 1999;Rosenfeld and van Hoesen 1979, rhesus monkeys;Weiss et al 2001, cotton-top tamarins). Numerous studies in our lab have supported the relationship between stimulus expertise and configural processing in chimpanzees.…”
Section: Introductionmentioning
confidence: 99%
“…Face recognition in nonhuman primates is also characterized by the inversion effect, providing evidence of holistic processing for upright faces ( cotton-top tamarins , Neiworth, Hassett and Sylvester 2007: chimpanzees , Parr et al 1998; Parr and Heintz 2008; Tomonaga 2007; Tomonaga et al 1993: Japanese monkeys , Tomonaga 1994: rhesus monkeys , Dahl et al 2007; Gothard et al 2009; Parr et al 2008; Vermeire and Hamilton 1998). An outstanding question, however, is whether all primates use the same second-order information to recognize faces.…”
mentioning
confidence: 99%